2022
DOI: 10.3389/fclim.2021.799055
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Temporal and Spatial Precipitation Patterns in the Southern Mid-Atlantic United States

Abstract: The investigation of regional vulnerability to extreme hydroclimatic events (e.g., floods and hurricanes) is quite challenging due to its dependence on reliable precipitation estimates. Better understanding of past precipitation trends is crucial to examine changing precipitation extremes, optimize future water demands, stormwater infrastructure, extreme event measures, irrigation management, etc., especially if combined with future climate and population projections. The objective of the study is to investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…The rain‐gauged data have limitations due to their spatial coverage, and satellite‐based precipitation, available for 1979–2020, have relatively coarse spatial or temporal resolution and are subject to the inherent systematic biases and uncertainties in their retrieval algorithms (Shi & Song, 2015; Wang et al., 2019). Spatial homogeneity and temporally consistent precipitation estimate of reanalysis precipitation products make them a valuable source for historical analyses (Dollan et al., 2022). Considering the relatively fine temporal and spatial resolution of NLDAS‐2, in addition to the data availability, we used this data set to extract the precipitation during the events.…”
Section: Discussionmentioning
confidence: 99%
“…The rain‐gauged data have limitations due to their spatial coverage, and satellite‐based precipitation, available for 1979–2020, have relatively coarse spatial or temporal resolution and are subject to the inherent systematic biases and uncertainties in their retrieval algorithms (Shi & Song, 2015; Wang et al., 2019). Spatial homogeneity and temporally consistent precipitation estimate of reanalysis precipitation products make them a valuable source for historical analyses (Dollan et al., 2022). Considering the relatively fine temporal and spatial resolution of NLDAS‐2, in addition to the data availability, we used this data set to extract the precipitation during the events.…”
Section: Discussionmentioning
confidence: 99%
“…On a regional scale, National Climate Assessment (NCA) reports an increasing trend of the heaviest precipitation (top 1%) in the Midwest and the Northeast (Melillo et al, 2014). A broad range of studies investigated the change in observed (Alexander et al, 2006;Dollan et al, 2022) and projected extremes (Sillmann et al, 2013;Ménégoz et al, 2020) at global and regional scales (Westra et al, 2013;Diaconescu et al, 2016) using a set of climate extremes defined by the Expert Team on Climate Change Detection and Indices (ETCCDI; Zhang et al, 2011). Detecting trends despite uncertainties originating from a variety of factors such as greenhouse emission scenarios and model differences (i.e., physics, parameterization, initialization) add to the difficulty of climate change assessment studies (Razavi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%